The effect of using pelletized media on the production of alpha-amylase by solid state fermentation - Arquiza, Apollo C. (2000)
The study investigated the effect of using pelletized media on the performance of a solid waste fermentation (SSF) system, particularly on an aerated packed bed bioreactor. the SSF utilized Aspergillus oryzae grown on rice bran-cassava starch medium (10:1 mass ration) to produce a-amylase. The pelletized medium had an effective diameter of 5 mm. compared to less than 0.0833 mm. for the unpelletized one. The column bioreactor used had a diameter of 100 mm and a total bed volume of 1.3 dm^3. At an aeration rate of 1.20 vessel volume per minute (vvm) and 84 hours fermentation time, the pelletized medium gave a yield of 589 dextrinizing unit (DUN)/g dry medium compared to 179 (DUN)/g dry medium for the unpelletized medium at the same conditions. Compared to that reported for SSF in static trays, the pelletized medium gave 6.52. greater value. at 3.40 vvm aeration rate, the yield (pelletized medium) was 611 DUN/g dry medium, which was 1.55 times that for the unpelletized medium and 5.44 times that for trays.
The effects of aeration rate and length of fermentation were further investigated for the pelletized medium. The results show that yield of a-amylase did not vary significantly (a = 5%) for aeration rates of 1.20, 2.06, 2.81, and 3.40 vvm. This lack of effect may be explained by the contributions of the conduction and convection heat transfer in the bioreactor. It was possible that the convection heat transfer in the resistance was negligible compared to the conduction resistance. As such, variations in the aeration rate would no longer affect the total rate of heat transfer. This implies that SSF using pelletized media does not require high aeration rates. A fermentation time of 120 hrs. produced a-amylase yields which were 60% greater than that for 84 hours. This was attributed to secondary growth from the spores produced by the initial inoculum.
The study showed that the use of pelletized media for production of a-amylase in SSF by Aspergillus oryzae in an aerated packed bed bioreactor gave yields that were greater than that for unpelletized media and trays. further study is therefore recommended to fully develop this process for large-scale SSF.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Amylases; Solid-state fermentation; Pelletizing